Practices of weight regulation among elite athletes in combat sports: A matter of mental advantage? - Pettersson, S.; Pipping Ekström, M.; Berg, C. M. (Journal of Athletic Training, 2013)
Context : The combination of extensive weight loss and inadequate nutritional strategies used to lose weight rapidly for competition in weight-category sports may negatively affect athletic performance and health. Objective : To explore the reasoning of elite combat-sport athletes about rapid weight loss and regaining of weight before competitions. Design : Qualitative study. Setting : With grounded theory as a theoretical framework, we employed a cross-examinational approach including interviews, observations, and Internet sources. Sports observations were obtained at competitions and statements by combat-sport athletes were collected on the Internet. Patients or Other Participants : Participants in the interviews were 14 Swedish national team athletes (9 men, 5 women; age range, 18 to 36 years) in 3 Olympic combat sports (wrestling, judo, and taekwondo). Data Collection and Analysis : Semistructured interviews with 14 athletes from the Swedish national teams in wrestling, judo, and taekwondo were conducted at a location of each participant's choice. The field observations were conducted at European competitions in these 3 sports. In addition, interviews and statements made by athletes in combat sports were collected on the Internet. Results : Positive aspects of weight regulation other than gaining physical advantage emerged from the data during the analysis: sport identity, mental diversion, and mental advantage. Together and individually, these categories point toward the positive aspects of weight regulation experienced by the athletes. Practicing weight regulation mediates a self-image of being "a real athlete." Weight regulation is also considered mentally important as a part of the precompetition preparation, serving as a coping strategy by creating a feeling of increased focus and commitment. Moreover, a mental advantage relative to one's opponents can be gained through the practice of weight regulation. Conclusions : Weight regulation has mentally important functions extending beyond the common notion that combat-sport athletes reduce their weight merely to gain a physical edge over their opponents.